2016
DOI: 10.1097/md.0000000000004867
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of duty hour regulations for pediatric resident wellness

Abstract: Duty hour regulations have been placed in residency programs to address mental health concerns and to improve wellness. Here, we elucidate the prevalence of depressive symptoms after implementing an overnight call shift system and the factors associated with burnout or depression among residents.A sequential exploratory mixed methods study was conducted in a tertiary care pediatric and perinatal hospital in Tokyo, Japan. A total of 41 pediatric residents participated in the cross-sectional survey. We determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…We implemented a new OCS system in July 2011 to improve residents’ working conditions. Under the new system, residents have 8 off hours after the morning rounds on the same day they have an OCS (Table ) . On the next day of their night shift, residents have no patient care duties after attending the hand‐off meeting and writing the charts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We implemented a new OCS system in July 2011 to improve residents’ working conditions. Under the new system, residents have 8 off hours after the morning rounds on the same day they have an OCS (Table ) . On the next day of their night shift, residents have no patient care duties after attending the hand‐off meeting and writing the charts.…”
Section: Methodsmentioning
confidence: 99%
“…Under the new system, residents have 8 off hours after the morning rounds on the same day they have an OCS (Table 1). 5 On the next day of their night shift, residents have no patient care duties after attending the hand-off meeting and writing the charts. Thus residents have at least 20 off hours after their night shift.…”
Section: Study Setting and Participantsmentioning
confidence: 99%
“…The limited Japanese research on mental health during residency also focuses on the influence of trainee psychological qualities (ability to cope with stress) and interpersonal relationships. 15,[38][39][40][41] The single Japanese study that trialed restriction of resident work hours identified no decrease in the prevalence of depression or burnout. 15 The other main distinguishing theme of Japanese residency was the breadth of clinical skills acquired, including facility with bedside procedures and radiology image interpretation.…”
Section: Themes and Acgme Core Requirementsmentioning
confidence: 99%
“…8,12,13 There is limited research on physician wellness in Japan and no discussion of work hour limits in residency requirements. 14,15 Instructional guidelines for residency training in Japan recommend aligning training with US residency attributes but are not legally binding. 16 There is variation in the training experience across programs, and Japan's modest specialty certification criteria have prompted concern about physician competency.…”
Section: Introductionmentioning
confidence: 99%
“…Graduate medical education (GME) exposes medical students and physicians in training to the realities of medical care, including long work hours and a set of professional expectations that often place patients' needs above the practitioner's own [7,8]. Traditionally, physician training programs in the United States extolled extensive work hours in order to facilitate learning and professional socialization of physicians.…”
Section: History Of Extensive Duty Hours For Graduate Medical Educatimentioning
confidence: 99%